Piezo and pyroelectric composite film for acoustic emission and X-ray radiation intensity detection - Sakamoto, W. K. [UNESP]; Higuti, R. T. [UNESP]; de Carvalho, A. A. [UNESP]; Estevam, G. P. [UNESP]; Pontes, W. [UNESP]; De Paula, M. H. (My University, 2010)
The continuous technological advances have required materials with properties that conventional material cannot display. Material property combinations are being the focus to the development of composite materials, which are considered a multiphase material that exhibits properties of the constituent phases. One interesting material to be studied as sensing material is the composite made of ferroelectric ceramic and polymeric matrix as a two phases composite material. In that case the combinations properties intended are the high piezo and pyroelectric activities of the dense ceramic with the impact resistant, flexibility, formability and low densities of the polymer. Considering the way that the ceramic is dispersed in the polymeric phase, according to Newnham [1] there are 10 possible connectivities, which indicate the way that each phase is self-connected in the composite. The composite studied here is made of a modified lead titanate (Pz34) ceramic and polyether-ether-ketone (PEEK) high performance polymer matrix. The composite film was obtained hot pressing both phases at 360° C during 2 h, and 12 MPa of pressure, being essentially a 0-3 composite that means the dispersed ceramic grains are not self-connected. Using the piezoelectric property the composite film was used to detect acoustic emission (AE), which is a transient elastic wave generated by sudden deformation taken place in materials under stress. AE can be applied for evaluating the health of structures in a non-destructive way. The composite film was surface mounted on an aluminum panel and ball bearing drop and pencil lead break were used as simulating AE sources. On the pyroelectric side, the composite film was used as sensing element in a pyroelectric chamber to measure X-ray intensity in the orthovoltage range (120 KVp - 300 KVp). Experimental results indicate that the combination properties of ceramic and polymer phases provide an alternative sensing material to be used as piezo and pyroelectric sensor. © 2010 Nova Science Publishers, Inc. All rights reserved.